2021
DOI: 10.2147/cmar.s326052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Nephrotoxicity Among Adult Cancer Patients at Mbarara Regional Referral Hospital

Abstract: Background: Nephrotoxicity is common among cancer patients, yet some anti-cancer drugs, for example, platinum derivatives, are nephrotoxic and have narrow therapeutic indices. If nephrotoxicity is not managed, it can progress to kidney injury, which results in unregulated blood pressure, hormonal imbalance, electrolyte imbalance, body fluid imbalance and death. However, the burden of nephrotoxicity among adult cancer patients in Uganda is not documented in the literature. Objective: This study assessed the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
3
1
0
Order By: Relevance
“…Patients who had a problem with friction and shear were 5.71 times more at high risk of developing pressure ulcers than those who had no apparent problem with friction or shear. These ndings are consistent with the ndings of studies conducted in Hawassa [32], Pakistan, [50], and, Kenya [51], These ndings revealed that patients who had problems with friction and shear were at greater risk than those with no apparent problems with friction or shear. Possible explanations include the possibility that individuals who fail to keep their body upright on a bed or wheelchair may have their skin slide over the support surface, leading to blood vessel damage, irritation, and skin necrosis, which can cause a pressure ulcer.…”
Section: Discussionsupporting
confidence: 90%
“…Patients who had a problem with friction and shear were 5.71 times more at high risk of developing pressure ulcers than those who had no apparent problem with friction or shear. These ndings are consistent with the ndings of studies conducted in Hawassa [32], Pakistan, [50], and, Kenya [51], These ndings revealed that patients who had problems with friction and shear were at greater risk than those with no apparent problems with friction or shear. Possible explanations include the possibility that individuals who fail to keep their body upright on a bed or wheelchair may have their skin slide over the support surface, leading to blood vessel damage, irritation, and skin necrosis, which can cause a pressure ulcer.…”
Section: Discussionsupporting
confidence: 90%
“…The study in China reported that age 50 and older is associated with cisplatin-induced nephrotoxicity, increased risk up to 11 times [24]. The finding is similar to the result of other study done in Uganda [16]. Older age has higher risk of nephrotoxicity, supported by the fact that older patients are more susceptible due to specific anatomical and functional changes, including kidney vasculature, filtration, and tubulointerstitial function [25].…”
Section: Discussionsupporting
confidence: 78%
“…The present, retrospective, and cohort study reported that nephrotoxicity is found in almost one third of the population, 45.2% of those who received cisplatin combination chemotherapy. This number is higher to the study by Kidera et al from Japan and Isiiko et al, from Uganda [5], [16], reported a cisplatininduced nephrotoxicity in 32% and 35.9% patients. Two studies from Netherlands found higher prevalence, 53.7% and 69% in head-and-neck cancer patients that treated with high-dose cisplatin.…”
Section: Discussioncontrasting
confidence: 66%
“…Despite the implementation of hydration protocols, CDDP-induced nephrotoxicity presents itself as acute or, in certain instances, chronic kidney injury, leading to life-threatening impairment of kidney function and a need for inclusion into surveillance programs. The prevalence of CDDP-induced nephrotoxicity ranges from 15 to 49%, depending on the study [ 24 , 25 , 26 ] and on the age of the patients [ 27 , 28 ]. Early indications of CDDP nephrotoxicity include a rapid reduction in the renal plasma flow and an elevation in urinary enzymes, which is characteristic of primary tubular toxicity.…”
Section: Discussionmentioning
confidence: 99%